Anesthetic Management of Parturients with Takayasu’s Arteritis: A Series of Three Cases - Nilesh M. Solanki; Nikita Kothari; Nirali Joshi; Monal Ramani; Disha Italiya; Aadil Chauhan (Journal of Obstetric Anaesthesia and Critical Care)
Context: Takayasu's arteritis (TA) is a chronic, progressive inflammatory arteritis. Aims: We describe the anesthesia management of three cases of TA who has presented for cesarean sections. Settings and Design: Epidural anesthesia, general anesthesia and Combined Spinal Epidural Anesthesia (CSE). Methods and Material: Takayasu's arteritis (TA) is a rare idiopathic chronic progressive pan-end arteritis involving aorta along with its main branches with more prediction for Asian women. Though progression of disease is not affected by pregnancy per se, the effect of multiple pathogenic prices of TA are associated with serious cardiovascular complications. Severe uncontrolled hypertension, end organ dysfunction, stenosis of measured blood vessels, aneurysm and difficulties in monitoring arterial blood pressure maybe challenging for management of anesthesia for patients with TA. Statistical Analysis Used: Result: Three different methods of anesthesia were applied to each patient. All procedures went uneventful but epidural anaesthesia worked in a better way. Conclusion: TA patient posted for cesarean section can be succefully managed with epidural anesthesia.